Development of a conceptual integrated influential factors (IIF) model of internal stakeholder for construction projects successful completion in Yemen - Al-Fadhal, Najib; Zainal, Rozlin; Ng, Kim-Soon; Ali Hasaballah, Abdel Hafiz (American Scientific Publishers, 2018)
Accomplishing construction projects within the time specified is seldom the case in Yemen. The funds allocated for the projects are usually not properly utilized. Many large construction projects in Yemen are either delayed, suspended or abandoned. Nonetheless, little exertion has been made to normalize the phenomenon. The objective of this paper is to develop an integrated influential factors (IIF) model for internal stakeholders to management construction projects successfully to completion in Yemen. The causes that affect the successful completion of project have been gathered and identified from the previous research works via literature. This model is expected to aid the successful completion of construction project in Yemen.